The Effect of Zero Sequence Impedance Parameters on Distance Protection Settings: A Case Study - Guzel, Semih; Gursanli, Ozgur; Ozturk, Onur; Karacasu, Ozgur; Akdeniz, Mevlut; Hocaoglu, Mehmet Hakan (IEEE, 2020)
Distance protection relays are widely used in transmission systems. Although there are many factors that affect the performance of distance protection relays in determining the fault location, the most important factor is the impedance values of the transmission line used as the setting value. It is important to consider the ground wire and parallel lines in the calculation of these setting values, which are generally determined using the theory of symmetrical components. These two parameters are known to be effective on transmission line zero sequence impedances. In this study, the effects of the ground wire type and parallel transmission lines on the zero sequence impedance values are investigated and the effects on the performance of the distance protection relays were evaluated by computer analysis on one of the power corridor of Turkish National Transmission Network. Positive improvements on the performance of the distance protection relay have been made by implementation of the results of this study to the field.
12th International Conference on Electrical and Electronics Engineering (ELECO) -- NOV 26-28, 2020 -- Bursa, TURKEY
Keywords: Parallel Transmission-Lines; Fault Location Algorithm; Scheme